Cerebral Venous Thrombosis Complicating Severe Preeclampsia in the Postpartum Period: A Diagnostic Challenge. Issue 2 (June 2015) - Ilkhchoui, Y.; Szabo, E.E.; Gerstein, N.S.; Jaime, F.
Abstract : ( J Clin Anesth . 2014;26(2):143–146)